Race and leadership in the news media 2021: evidence from five markets - Nielsen, R; Robertson, C; Selva, M (Reuters Institute for the Study of Journalism, 2021)
In this RISJ factsheet, we analyse the racial breakdown of top editors in a strategic sample of 100 major online and offline news outlets in five different markets across four continents. Building off work started in 2020, we find in 2021 that only 15% of the 80 top editors across the 100 brands covered are non-white. Non-white people make up the majority of top editors in four out of five markets (the exception being South Africa) and that three markets (Brazil, Germany, UK) have no non-white top editors at all. In all markets covered, even South Africa, the percentage of non-white people in the general population is much higher than it is among top editors and there is no simple relationship between the percentage of non-white journalists and the percentage of non-white top editors. Findings indicate no clear overall trend towards greater racial equality in top editorial positions from 2020 to 2021.